Trastorno por déficit de atención e hiperactividad y su repercusión en el proceso de enseñanza y aprendizaje en un niño - Bermello Romero, Cruz Adelaida (2019)
The present case study: "Attention deficit hyperactivity disorder and its impact on the teaching and learning process in a Child", a child of the football discipline of the Cantonal Sports League of Windows was performed, which was successful attention deficit hyperactivity disorder in the teaching and learning process. To reach this result, four sessions will be needed to obtain the necessary information, where the test of the human figure of Karen Machover and the EDAH test will be seen, which served for the diagnosis. It is recommended to give talks to family members and teachers, so that they have the necessary information on how to treat the child with his condition